AUDIT EXPECTATION GAP: CAUSES AND POSSIBLE SOLUTIPONS - Teck Heang Lee; Azham Md. Ali (Indonesian Management and Accounting Research, 2009)
The auditing profession believes the increase of litigation and criticism against the auditors can be contributed to the audit expectation gap. The audit expectation gap is defined as the difference between what the public expects from an audit and what audit profession accepts the audit objective to be. The audit expectation gap is critical to the auditing profession because the greater the unfulfilled expectations from the public, the lower is the credibility, earning potential and prestige associated with the work of auditors. The objectives of the paper are two-fold. Firstly, it attempts to uncover the causes of an audit expectation gap. Secondly, it reviews the possible solutions in narrowing the gap. This paper aims to provide an insight into issues of the audit expectation gap which in turn enable the audit profession and the profession's regulatory bodies to take effective steps in narrowing the audit expectation gap.